PENTINGNYA MANAJEMEN KURIKULUM DALAM PENGELOLAAN PENDIDIKAN - Nona Kumala Sari (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2021)
Abstract: Curriculum management is a process or system of curriculum management that is cooperative, comprehensive, systemic, and systematic to refer to the achievement of curriculum objectives that have been formulated. The objectives of the curriculum are as ideas, written plans, activities and results. The functions of curriculum management include the functions of adjustment, integration, differentiation, preparation, selection and accounting functions. The principles of curriculum management include oriented vision, mission and goals of education, productivity, democratic, cooperative, effectiveness and efficiency. There are four stages in the curriculum itself, namely the Planning Phase, the organizing stage, the implementation phase, and the control stage. In the curriculum there are a number of things that support the curriculum management process, including the following: Student factors, socio-cultural factors, political factors, economic factors, technological development factors. Barriers that occur in curriculum management include: Continuity and not leaving between educators in the field with educators who provide policies on it, limited facilities and infrastructure, weak teacher supervision in the field which causes a fairly low level of discipline, educational qualifications teachers who are not in accordance with their fields, which leads to the level of professionalism of teachers in learning activities or the delivery of subject matter.Kata Kunci: Manajemen, Kurikulum,Pendidikan.